(untitled) (Texas Journal of Philology, Culture and History, 2026)
The article examines the theoretical and methodological foundations of the concepts of “term” and “terminology” within the study of the diplomatic terminological system. It analyzes various scholarly approaches to defining a term, its structural and semantic features, and the criteria that distinguish terms from general vocabulary. Special attention is given to the specificity of diplomatic lexis as an integral part of the professional language of international relations. The study identifies the key characteristics of diplomatic terms, including their systemic nature, functional orientation, high degree of standardization, and dependence on political and legal contexts. The review of existing terminological theories provides a methodological basis for further research into diplomatic terminology as a coherent and dynamically evolving system. The results serve as a theoretical foundation for subsequent investigation into the structure, classifications, mechanisms of functioning, and evolution of the diplomatic terminological system